Labeling "Desi' and "muslim" as seen in Samira Ahmed's internment : a languange and identity study - Asfarina Prasetya (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2021)
iim,1/ yna, c.1